A Large Intra-Abdominal, Extra Adrenal Myelolipoma- Case Report - Fatima, Maryam; Sheikh, Ahmareen Khalid; Tanwani, Ashok Kumar (International Journal of Pathology, 2018)
Introduction: Myelolipomas are benign tumors composed of mature adipose tissue and normal hematopoieticcells. Myelolipomas develop in older age group and usual site of occurrence is adrenal gland. Their developmentin young individuals and at extra-adrenal site is quite rare. Very few cases of extra-adrenal myelolipomas havebeen reported in the literature. An extra-adrenal myelolipoma is solitary, well defined mass in abdomen, commonlyoccurring in retroperitoneal area. The small sized lesions are usually asymptomatic, but if large in sizethey can produce symptoms related to mass effect. The patient has no hematological abnormalities.Case Presentation: We present a case of a large intra abdominal extra-adrenal myelolipoma measuring 28 x 22 x6cm in a 29 years old male patient who presented with abdominal pain and distention. His abdominal CT scanshowed a large well defined retroperitoneal lesion measuring 13.1 x 10.3 x 22cm in Anteroposterior xTransverse xCraniocaudal extent, in the region of left paraventricular gutter having fat density may represent liposarcoma.His both adrenals appeared normal. He was operated for this lesion and the specimen was sent to us for histopathologicalevaluation. Grossly it was solitary, encapsulated mass. Cut section showed fatty tissue with hemorrhagicareas. Microscopically, mature adipose tissue with areas of mature hematopoietic cell of all lineages wasseen.Conclusion: Since extra-adrenal myelolipoma is a rare entity diagnosis of this lesion based on radiographic studiesalone is at times difficult. It is important to distinguish extra-adrenal myelolipoma from other fat-containingtumors in particular retroperitoneal liposarcoma, extra-medullary hematopoietic neoplasms and angiomyolipoma.Histopathologic evaluation is the gold standard for confirmation of the diagnosis. We have discussed thebackground, pathology, complications, differential diagnosis and management of this rare entity.